Biogeographical Patterns of Legume-Nodulating Burkholderia spp.: from African Fynbos to Continental Scales - Lemaire, Benny; Chimphango, Samson B. M.; Stirton, Charles; Rafudeen, Suhail; Honnay, Olivier; Smets, Erik; Chen, Wen-Ming; Sprent, Janet; James, Euan K.; Muasya, A. Muthama (Applied and environmental microbiology, 2016)
Rhizobia of the genus Burkholderia have large-scale distribution ranges and are usually associated with South African papilionoid and South American mimosoid legumes, yet little is known about their genetic structuring at either local or global geographic scales. To understand variation at different spatial scales, from individual legumes in the fynbos (South Africa) to a global context, we analyzed chromosomal (16S rRNA, recA ) and symbiosis ( nifH , nodA , nodC ) gene sequences. We showed that the global diversity of nodulation genes is generally grouped according to the South African papilionoid or South American mimosoid subfamilies, whereas chromosomal sequence data were unrelated to biogeography. While nodulation genes are structured on a continental scale, a geographic or host-specific distribution pattern was not detected in the fynbos region. In host range experiments, symbiotic promiscuity of Burkholderia tuberum STM678 T and B . phymatum STM815 T was discovered in selected fynbos species. Finally, a greenhouse experiment was undertaken to assess the ability of mimosoid ( Mimosa pudica ) and papilionoid ( Dipogon lignosus , Indigofera filifolia , Macroptilium atropurpureum , and Podalyria calyptrata ) species to nodulate in South African (fynbos) and Malawian (savanna) soils. While the Burkholderia -philous fynbos legumes ( D . lignosus , I . filifolia , and P . calyptrata ) nodulated only in their native soils, the invasive neotropical species M . pudica did not develop nodules in the African soils. The fynbos soil, notably rich in Burkholderia , seems to retain nodulation genes compatible with the local papilionoid legume flora but is incapable of nodulating mimosoid legumes that have their center of diversity in South America. IMPORTANCE This study is the most comprehensive phylogenetic assessment of root-nodulating Burkholderia and investigated biogeographic and host-related patterns of the legume-rhizobial symbiosis in the South African fynbos biome, as well as at global scales, including native species from the South American Caatinga and Cerrado biomes. While a global investigation of the rhizobial diversity revealed distinct nodulation and nitrogen fixation genes among South African and South American legumes, regionally distributed species in the Cape region were unrelated to geographic and host factors.